Le parcours du masochiste : de la Perversion à la Transgression - Guillermo de Eugenio Pérez (Criminocorpus)
I would like to analyse the social dimension of masochist subjects and their practices in opposition to normative values. In order to question the emancipatory potential of deviation, I will suggest to follow the path of the concept and «sadomasochistic» practices back from the nineteen century until today. It is therefore a matter of reestablishing the genealogy of a changing object, not easy to comprehend. The emphasis of this reflection is on the historical and epistemic discontinuities of «sadomasochism», which is at the same time an object for psy- sciences, a literary subject and a set of erotic practices. By analyzing the these aspects, I would like to stress the political (in the feminist sense: «private is political») and radical force of such practices, which is the core of the present intervention.